Assessing Nonviolence in the Palestinian Rights Struggle. (1st April 2016) - Victoria Mason; Richard Falk
Abstract : "If only there was a Palestinian Gandhi" has been a common refrain in recent years. Yet in reality, Palestinians have a long history of relying on nonviolence. However, this nonviolence has received no constructive response from either Israel or the international community. The failure to acknowledge and welcome the Palestinian nonviolent movement serves to prolong the conflict and its negative effects, and lays bare the refusal of the international community to address the rights abuses at the heart of the Israeli–Palestinian conflict. This article narrates Palestinian use of both violence and nonviolence in their struggle to achieve national self-determination and other basic rights, and assesses the potential of nonviolent action to enable a just resolution of their situation.